2018
DOI: 10.1590/0103-6513.20170046
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to occupational health and safety management in small Brazilian enterprises

Abstract: Paper aims: To determine main barriers to the implementation of occupational health and safety management systems OHSMS in the context of small Brazilian enterprises from the perspectives of owners/managers, labor auditors, and OHS consultants. Originality: Survey with three different perspectives on small Brazilian enterprises. Research method: Survey conducted with stakeholders who influence the safety culture in small enterprises to identify the main barriers to the implementation of OHSMS. Main findings: O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
11
0
2
Order By: Relevance
“…Employees with insufficient knowledge and with no knowledge about occupational legislation were rated together as ‘not knowledgeable’ because of the fact that for occupational legislation to be properly implemented and complied with, workers needed to be fully knowledgeable about it. According to Garnica and Barriga ( 2018 :1), lack of knowledge and few available resources result in non-compliance to occupational legislation in work settings. Lack of resources to protect the health and safety of workers is regarded as lack of knowledge by managers and/or reluctance of workers to use personal protective equipment (PPE).…”
Section: Discussionmentioning
confidence: 99%
“…Employees with insufficient knowledge and with no knowledge about occupational legislation were rated together as ‘not knowledgeable’ because of the fact that for occupational legislation to be properly implemented and complied with, workers needed to be fully knowledgeable about it. According to Garnica and Barriga ( 2018 :1), lack of knowledge and few available resources result in non-compliance to occupational legislation in work settings. Lack of resources to protect the health and safety of workers is regarded as lack of knowledge by managers and/or reluctance of workers to use personal protective equipment (PPE).…”
Section: Discussionmentioning
confidence: 99%
“…Los autores señalan que, los hallazgos de la investigación pueden desempeñar su papel en el fortalecimiento de los argumentos a favor de las reformas en el sector, y que, podrían permitir a los empleadores del sector aumentar su conocimiento sobre las prácticas de SSO y, como resultado, tratar de ofrecer entornos más seguros para sus trabajadores. Garnica & Barriga (2018), quienes determinan las principales barreras para la implementación de sistemas de gestión de salud y seguridad ocupacional OHSMS en el contexto de pequeñas empresas brasileñas desde la perspectiva de propietarios / gerentes, auditores laborales y consultores de OHS, encontrando que los propietarios / gerentes tienden a culpar a los empleados y al gobierno por la dificultad de implementar OHSMS, y los actores externos tienden a culpar a la administración y la asignación de recursos; y que , las opiniones convergen en el comportamiento inadecuado de la gestión, la información ineficaz y la comunicación y la priorización de la producción. Estas barreras deberían superarse no solo para facilitar la implementación de OHSMS sino también para mejorar las condiciones de gestión de todas las operaciones de pequeñas empresas.…”
Section: Nuevos Factores Que Impactan La Seguridad Y Salud Laboralunclassified
“…In all, the aim is to achieve the organization's objectives. Unfortunately, Oliveira et al [22] observed that the obedience to rules and regulations differs according to staff and the organization. Furthermore, the process of Planning and Procedure, as one of the essential elements requires an arrangement of all the important varied ideas related to a set of assigned responsibilities designed to achieve the organization's goal.…”
Section: Introductionmentioning
confidence: 99%
“…This, in a way, eliminates favouritism, among other things from the system. Many challenges to OHSMS implementation have been identified by Garmica and Barriga [22]. These include inadequate attitude of both the employer and the employees, establishment of rigid rules and regulations, recruitment of unqualified personnel to man important positions, nonchalant attitude of management, poor or inadequate auditing and over-ambition to make profit and negligence of the health and safety of workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation